PELATIHAN PEMBUATAN WEBSITE MENGGUNAKAN GOOGLE SITES UNTUK MENINGKATKAN LITERASI TIK MAHASISWA PENDIDIKAN JASMANI - Indriaturrahmi Indriaturrahmi; Fitri Ramdani; Gina Sonia; Karatika Riskiani (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of information and communication technology (ICT) requires students to possess adequate digital literacy to support learning processes and instructional media development. However, field conditions indicate that many students of the Physical Education Study Program at Universitas Pendidikan Mandalika still have limited ICT skills, particularly in utilizing website-based learning media. This community service activity aimed to improve students’ ICT literacy through training on developing websites using Google Sites. The program was conducted in three sessions involving 40 students. The method applied was practice-based training and mentoring, including the introduction of Google Sites, website design, content management, and website publication, as well as independent assignments. The results indicated a significant improvement in students’ abilities to understand website concepts, operate the Google Sites platform, manage digital content, and publish websites. In addition, students were able to develop personal websites with Physical Education themes, including profiles, learning materials, and documentation of physical activities. Therefore, the Google Sites training proved effective in enhancing ICT literacy and can serve as a model for community service in supporting the development of digital competencies among prospective Physical Education teachers. ABSTRAK Perkembangan teknologi informasi dan komunikasi (TIK) menuntut mahasiswa memiliki literasi digital yang memadai untuk mendukung proses pembelajaran dan pengembangan media ajar. Namun, kondisi di lapangan menunjukkan bahwa sebagian mahasiswa Program Studi Pendidikan Jasmani Universitas Pendidikan Mandalika masih memiliki keterbatasan dalam keterampilan TIK, khususnya dalam pemanfaatan media pembelajaran berbasis website. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan literasi TIK mahasiswa melalui pelatihan pembuatan website menggunakan Google Sites. Kegiatan dilaksanakan dalam tiga kali pertemuan dengan melibatkan 40 mahasiswa. Metode yang digunakan berupa pelatihan dan pendampingan berbasis praktik langsung yang meliputi pengenalan Google Sites, perancangan tampilan, pengelolaan konten, hingga publikasi website, serta penugasan mandiri. Hasil kegiatan menunjukkan adanya peningkatan kemampuan mahasiswa dalam memahami konsep website, menggunakan platform Google Sites, mengelola konten digital, dan mempublikasikan website. Selain itu, mahasiswa mampu menghasilkan website pribadi bertema pendidikan jasmani yang memuat profil, materi pembelajaran, dan dokumentasi aktivitas fisik. Dengan demikian, pelatihan Google Sites efektif dalam meningkatkan literasi TIK dan dapat dijadikan sebagai model pengabdian kepada masyarakat dalam mendukung pengembangan kompetensi digital calon pendidik pendidikan jasmani.